Self-awareness Strategy Using Podcasting to Improve Tense and Lax Vowel Pronunciation Sounds in Beginner EFL-Adult Learners - Dalia Lisette Aguilar Vacacela; Maria Rossana Ramirez (Journal of Foreign Language Teaching and Learning, 2020)
This action research study measured the effectiveness of a self-awareness strategy and podcasting to help beginners EFL-adult learners to pronounce tense-lax vowels in English accurately. The participants were 17 adult students with an A1.2 English level. This innovation was implemented in a language school in a coastal city in Ecuador, South America. The results were obtained using quantitative data gathered from a pre and a post-test, which were divided in two parts; a scripted and extemporaneous one. The final scores produced a large effect size of 2.27 for tense vowels and 4.89 for lax vowels, indicating that most of students were able to pronounce more than the 80% of tense and lax vowels accurately. These results demonstrated that the self-awareness strategy and the podcasting had a great impact on tense-lax vowels pronunciation in adults. Despite the favorable results, further and deeper research is needed with a larger sample, period of time, and training.